Arctic Ozone Depletion from UARS MLS Measurements - Manney, G. L. (2004)
Microwave Limb Sounder (MLS) measurements of ozone during four Arctic winters are compared. The evolution of ozone in the lower stratosphere is related to temperature, chlorine monoxide (also measured by MLS), and the evolution of the polar vortex. Lagrangian transport calculations using winds from the United Kingdom Meteorological Office's Stratosphere-Troposphere Data Assimilation system are used to estimate to what extent the evolution of lower stratospheric ozone is controlled by dynamics. Observations, along with calculations of the expected dynamical behavior, show evidence for chemical ozone depletion throughout most of the Arctic lower stratospheric vortex during the 1992-93 middle and late winter, and during all of the 1994-95 winter that was observed by MLS. Both of these winters were unusually cold and had unusually cold and had unusually strong Arctic polar vortices compared to meteorological data over the past 17 years.